Intestinal obstruction due to a congenital mesenteric hernia in a newborn with cystic fibrosis: A case report - Maho Kurashima; Chadi Nahal; Christian Saliba; Raymond Okeke; Shin Miyata (Elsevier, 2024)
Introduction: Congenital mesenteric defect is a rare cause of neonatal small bowel obstruction. We present a case of a newborn with cystic fibrosis experiencing small bowel herniation through a congenital mesenteric defect leading to bowel ischemia. Case: A 0-day-old term, 3.2 kg female with a family history of cystic fibrosis carrier was evaluated for abdominal distension. Prenatal ultrasound showed bowel dilation with increased wall thickness, and post-delivery abdominal X-ray showed a cystic dilation of the bowel. Contrast fluoroscopy of the lower gastrointestinal tract showed small intestinal filling defects and microcolon. She was treated for suspected meconium ileus. Bowel dilation progressed necessitating exploratory laparotomy on day of life 4, with findings of jejunal perforation and ischemic ileal dilatation secondary to herniation through a congenital mesenteric defect. Ileal resection and ileal-ileal anastomosis with jejunostomy creation were performed. The postoperative course of ostomy takedown was complicated by anastomotic breakdown, requiring ileostomy creation. Genetic testing revealed cystic fibrosis. Because of high ileostomy output and meconium impaction in the distal bowel, Bishop-Koop ostomy construction and ileocolic anastomosis were performed. The residual small intestine was 61 cm with an ileocecal valve. At age 2, she remained dependent on total parental nutrition and gastrostomy tube feeding, with intestinal failure and chronic liver failure. Conclusion: Herniation through a congenital mesenteric defect is an extremely rare differential diagnosis for neonatal bowel obstruction. Concomitant cystic fibrosis can compromise postoperative management and cause complications resulting in short gut syndrome due to multiple surgical interventions. Level of evidence: level 5.